2020
DOI: 10.1371/journal.pone.0237363
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of paravertebral block versus intercostal nerve block in thoracic surgery and breast surgery: A systematic review and meta-analysis

Abstract: Objective To evaluate the analgesic efficacy and safety of paravertebral block (PVB) versus intercostal nerve block (INB) in thoracic surgery and breast surgery. Methods The PubMed, Web of Science, Embase and the Cochrane Library were searched up to February 2020 for all available randomized controlled trials (RCTs) that evaluated the analgesic efficacy and safety of PVB compared with INB after thoracic surgery and breast surgery. For binary variables, odds ratio (OR) and 95% confidence interval (CI) was used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 38 publications
0
19
1
Order By: Relevance
“…The intercostal nerves come from the anterior branch of the thoracic paravertebral nerve, it was performed primarily by surgeons at multiple levels of direct visualization. The block was considered easy, with relatively low side effects and have been used as an analgesic replacement to TPVB in VATS with beneficial effect [ 22 ]. Although ICNB has shown to lower pain scores in the early postoperative period, but its duration of action was limited.…”
Section: Discussionmentioning
confidence: 99%
“…The intercostal nerves come from the anterior branch of the thoracic paravertebral nerve, it was performed primarily by surgeons at multiple levels of direct visualization. The block was considered easy, with relatively low side effects and have been used as an analgesic replacement to TPVB in VATS with beneficial effect [ 22 ]. Although ICNB has shown to lower pain scores in the early postoperative period, but its duration of action was limited.…”
Section: Discussionmentioning
confidence: 99%
“…The ICNB involves injection of local anesthetic in the intercostal space inferior to the rib between the internal and innermost intercostal muscles (Figure 1) and can be performed percutaneously with landmark or ultrasoundguidance, or intraoperatively with direct or video visualization (100). Meta-analysis of ICNB versus PVB for thoracic and breast surgery showed that PVB was superior to ICNB with improved analgesia at one and 24 hours, lower opioid consumption, and potentially improved postoperative respiratory function (101). More recently, a large systematic review and meta-analysis demonstrated that ICNB has benefits including improved pain control and reduced opioid consumption in the first 24 hours after thoracic surgery compared to systemic therapy alone (102).…”
Section: Icnbmentioning
confidence: 99%
“…In addition, placement of both TEA and PVB requires appropriate discontinuation of anticoagulants. Intercostal nerve blocks (ICNBs) have been used as an analgesic alternative to TEA and PVB in VATS with beneficial effect [ 13 , 14 ]. However, although ICNBs have shown to lower pain scores in the early postoperative period [ 15 ], they have a limited duration of effect [ 16 ].…”
Section: Introductionmentioning
confidence: 99%